Primary Dysmenorrhea in Relation to Oxidative Stress and Antioxidant Status: A Systematic Review of Case-Control Studies - Maria Karolina Szmidt; Dominika Granda; Ewa Sicinska; Joanna Kaluza (MDPI AG, 2020)
Primary dysmenorrhea is defined as painful menstrual cramps of uterine origin in the absence of pelvic pathology and is the most common gynecological disorder among women of reproductive age. The aim of this study was to systematically review case-control studies that have investigated the oxidative stress, antioxidant status, and inflammation markers among women with primary dysmenorrhea and controls. The study protocol was registered with PROSPERO (no. CRD42020183104). By searching PubMed and Scopus databases as well as reference lists, six case-control studies with fifteen eligible markers (seven oxidative stress, seven antioxidant status, one inflammation) were included in this review. The quality of the included studies was assessed as medium or high. The systematic review included 175 women with primary dysmenorrhea and 161 controls. The results indicate an elevated level of oxidative stress, especially of lipid peroxidation among dysmenorrheal women. For the antioxidant status, limited evidence was found for a lower status among primary dysmenorrhea women, and only one study examined one inflammation marker (hs-CRP), which makes it impossible for such a conclusion. To establish whether oxidative stress, antioxidant status or inflammation participate in the pathophysiology of primary dysmenorrhea, high-quality studies with larger study groups and clear case definitions are needed.